2015
DOI: 10.2215/cjn.03350414
|View full text |Cite
|
Sign up to set email alerts
|

Low Triiodothyronine Syndrome and Long-Term Cardiovascular Outcome in Incident Peritoneal Dialysis Patients

Abstract: Background and objectives A direct association between low triiodothyronine (T3) syndrome and cardiovascular (CV) mortality has been reported in hemodialysis patients. However, the implications of this syndrome in peritoneal dialysis (PD) patients have not been properly investigated. This study examined the association between low T3 syndrome and CV mortality including sudden death in a large cohort of incident PD patients.Design, setting, participants, & measurements This prospective observational study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…This study provides important contributions to the existing body of literature by (1) corroborating that thyroid hormone deficiency may be a novel cardiovascular risk factor in patients with CKD and (2) adding incremental knowledge to our understanding of the mechanistic pathways underlying the low T3-mortality association in CKD (14). This is the first study showing an association between low T3 and cardiovascular mortality in patients on PD (14), and it is the first time that the low-T3 syndrome has been shown to predict sudden death in patients with CKD, the leading cause of cardiovascular mortality in this population (1).…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…This study provides important contributions to the existing body of literature by (1) corroborating that thyroid hormone deficiency may be a novel cardiovascular risk factor in patients with CKD and (2) adding incremental knowledge to our understanding of the mechanistic pathways underlying the low T3-mortality association in CKD (14). This is the first study showing an association between low T3 and cardiovascular mortality in patients on PD (14), and it is the first time that the low-T3 syndrome has been shown to predict sudden death in patients with CKD, the leading cause of cardiovascular mortality in this population (1).…”
mentioning
confidence: 54%
“…In contrast to previously published reports, TSH and free T4 levels were not associated with all-cause or cardiovascular death (15,16). However, this study excluded patients whose thyroid functional tests showed overt hypothyroidism (i.e., high TSH and low free T4) or hyperthyroidism (i.e., low TSH) as well as those with known hypo-and hyperthyroidism, which may have restricted the range of observed TSH and free T4 values in this study population (14).…”
mentioning
confidence: 71%
See 3 more Smart Citations